ASIMOV: a proposal for assisting model coevolution with constrained metamodels (2011)
Metamodel evolution is a natural process that happens in model-driven approaches. A metamodel evolves when the modeler have the need to add new elements to match new requirements. Nowadays creating new elements have not become the only addition to the metamodels. Usually the metamodel evolution involves creating or adding constraints, in order to ensure the restrictions that cannot be expressed with mere syntax. The current model coevolution approaches leaves behind the assistance when the metamodels have a set of restrictions. In this paper we propose an approach for supporting the model coevolution in two parts: the assistance language and a model adaptation when it is conform to constrained metamodels.